Prognostic Value of Spontaneous Potential in Left Atrial Posterior Wall Isolation and Radiofrequency Ablation for Non-Paroxysmal Atrial Fibrillation - Chen ZY; Zhong YH; Gong KZ; Chen XH; Xu Z; Zhang FL (Therapeutics and Clinical Risk Management, 2025)
Zhi-Yang Chen,1,2,* Yu-Hong Zhong,1,3,* Ke-Zeng Gong,1 Xue-Hai Chen,1 Zhe Xu,1 Fei-Long Zhang1 1Department of Cardiology, Fujian Medical University Union Hospital; Fujian Heart Medical Center, Fujian Institute of Coronary Heart Disease; Fujian Clinical Medical Research Center for Heart and Macrovascular Disease, Fuzhou, 350001, People’s Republic of China; 2Department of Cardiology, Zhangzhou Yuanshan Hospital, Zhangzhou, 363100, People’s Republic of China; 3Department of Cardiology, Huian County Hospital, Quanzhou, 362100, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fei-Long Zhang, Department of Cardiology, Fujian Medical University Union Hospital; Fujian Heart Medical Center, Fujian Institute of Coronary Heart Disease; Fujian Clinical Medical Research Center for Heart and Macrovascular Disease, No. 29 Xinquan Road, Gulou District, Fuzhou, 350001, People’s Republic of China, Tel +86 10 8888888, Fax +86 10 6666666, Email cardizhang@163.comObjective: This study aimed to examine the long-term effects of left atrial posterior wall spontaneous potential (SP) in patients with non-paroxysmal atrial fibrillation (AF) who underwent pulmonary vein isolation (PVI) combined with left atrial posterior wall isolation (PVI+BOX) ablation.Methods: Clinical data were retrospectively collected from 140 patients with symptomatic non-paroxysmal atrial fibrillation (NPAF) who underwent first-time radiofrequency ablation between 2022 and 2023. Based on the surgical procedure, patients were categorized into the pulmonary vein isolation group (PVI group) and the pulmonary vein isolation + left atrial posterior wall isolation group (PVI+BOX group). The PVI+BOX group was further subdivided into the spontaneous potential group (SP group) and the no-spontaneous potential group (no-SP group) based on the presence of SP after left atrial posterior wall isolation. Patients underwent monthly follow-ups in the clinic or via telephone and received 72-hour dynamic electrocardiography (ECG) at 3 and 12 months postoperatively. AF recurrence was compared among the groups, and factors associated with recurrence following AF ablation were analyzed.Results: The PVI+BOX group included 78 cases, with 45 in the no-SP group and 33 in the SP group, while the PVI group comprised 62 cases. No significant difference was observed in the postoperative recurrence-free rate between the PVI+BOX and PVI groups. However, the SP group exhibited a higher postoperative recurrence-free rate compared to both the no-SP group (p = 0.039) and the PVI group (p = 0.020). No significant difference was found in the late recurrence-free rate between the no-SP and PVI groups. Multivariate logistic regression analysis indicated that the duration of AF and the presence of left atrial posterior wall SP were independent risk factors for post-ablation recurrence in patients with NPAF.Conclusion: The presence of SP post-left atrial posterior wall isolation suggests a better long-term outcome in patients with NPAF following PVI+BOX catheter ablation.Keywords: left atrial posterior wall, non-paroxysmal atrial fibrillation, pulmonary vein isolation, radiofrequency ablation, spontaneous potential